2018
DOI: 10.1111/area.12447
|View full text |Cite
|
Sign up to set email alerts
|

“A prison within a prison”? Examining the enfolding spatialities of care and control in the Barlinnie Special Unit

Abstract: This paper uses one of Scotland's most controversial experiments in penal reform – the Barlinnie Special Unit – to examine the enfolding nature of care and control in carceral space. Connecting with recent arguments relating to “caring architecture” and using the framework of historical carceral geographies, it showcases the spatial complexities of implementing caring practices alongside reforming tactics. Beginning with a discussion of the care and control nexus within institutional spaces and its historical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…Questions of control and care (Disney and Schliehe, 2019) and their enfolding spatialities (McGeachan, 2019) are the focus of ongoing work in institutional geographies (Philo and Parr, 2019;Philo and Parr, 2000). Schliehe (2017) in her research in prisons and secure units in Scotland found that care beyond baseline need, i.e.…”
Section: Enfolding Spatialities Of Control and Carementioning
confidence: 99%
See 2 more Smart Citations
“…Questions of control and care (Disney and Schliehe, 2019) and their enfolding spatialities (McGeachan, 2019) are the focus of ongoing work in institutional geographies (Philo and Parr, 2019;Philo and Parr, 2000). Schliehe (2017) in her research in prisons and secure units in Scotland found that care beyond baseline need, i.e.…”
Section: Enfolding Spatialities Of Control and Carementioning
confidence: 99%
“…However, the prison estate lags behind this trend and within this wider process there are different still smaller units emerging, particularly with experimental regimes, which might differ from the wider prison. Small units and their 'difficult prisoners' have often been absent from accounts of penal system history (Nellis, 2010;Turner and Peters, 2015;McGeachan, 2019). Therefore, research on their environments has only recently begun to emerge.…”
Section: Dwelling In a Small Spacementioning
confidence: 99%
See 1 more Smart Citation
“…As such, the present special section, entitled “Troubling Institutions at the Nexus of Care and Control,” can, we feel, be readily and usefully cast as a series of explorations – adopting an overtly institutional focus – tracking across the rough, tricky and lively grounds of care and control as surveyed by Puig de la Bellacasa. Cheryl McGeachan () writes in the title of her paper about “the enfolding spatialities of care and control,” Jennifer Turner and Dominique Moran () about “careful control,” Frank Ollivon () about an “ethics of care in a control‐orientated technology,” Virve Repo () about “spatial control and care,” and Emma Wainwright and Elodie Marandet () about “care and control.” While Puig de la Bellacasa's approach is not itself “a sociological or ethnographic inquiry into a specific domain of agencies of care,” her trajectory is one that “invites others to consider care – or its absence – as a parameter of existence with significance for their own terrains” (Puig de la Bellacasa, , p. 6). The authors contributing to the present special section are indeed contemplating such matters on “their own terrains,” offering valuable insights relevant to these local terrains – all of which are placed in named locations (e.g., the Barlinnie Special Unit, north‐east of Glasgow, Scotland) and specifiable categories of site (e.g., UK prisons, homes of electronically tagged French offenders, Finnish nursing homes; UK housing associations) – but also, as gathered together here, comprising resources for comparative interpretation (perhaps with reference to the more widely travelling speculations of Puig de la Bellacasa and others).…”
Section: Care Control and Institutional Geographiesmentioning
confidence: 99%
“…This situation is particularly apparent in McGeachan's () piece that traces the attempts of the Barlinnie Special Unit to introduce therapeutic elements into an environment considered to hold Scotland's most “dangerous” prisoners. Penal culture often experiences cycles of reform (Jewkes & Johnston, ), at times leaning towards the therapeutic.…”
Section: Towards Geographies Of Troubling Institutionsmentioning
confidence: 99%